2022
DOI: 10.1042/ebc20220016
|View full text |Cite
|
Sign up to set email alerts
|

WNT signaling and cancer stemness

Abstract: Cancer stemness, defined as the self-renewal and tumor-initiation potential of cancer stem cells (CSCs), is a cancer biology property featuring activation of CSC signaling networks. Canonical WNT signaling through Frizzled and LRP5/6 receptors is transmitted to the β-catenin-TCF/LEF-dependent transcription machinery to up-regulate MYC, CCND1, LGR5, SNAI1, IFNG, CCL28, CD274 (PD-L1) and other target genes. Canonical WNT signaling causes expansion of rapidly cycling CSCs and modulates both immune surveillance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 83 publications
1
48
1
Order By: Relevance
“…β-catenin participates in Wnt signaling during PCa progression and development of therapy resistance [ 35 ], and its expression in prostatic tissues mirrors GR expression [ 14 , 22 , 34 , 42 , 43 , 44 , 45 ]. Notably, β-catenin transcriptionally activates stemness and chemoresistance-associated genes, including CD44 , NANOG , MYC , and CXCR4 [ 46 , 47 , 48 , 49 , 50 ]. A recent study indicated that inhibition of the Wnt/β-catenin pathway in the presence of DTX in PCa cells downregulated genes linked to chemoresistance [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…β-catenin participates in Wnt signaling during PCa progression and development of therapy resistance [ 35 ], and its expression in prostatic tissues mirrors GR expression [ 14 , 22 , 34 , 42 , 43 , 44 , 45 ]. Notably, β-catenin transcriptionally activates stemness and chemoresistance-associated genes, including CD44 , NANOG , MYC , and CXCR4 [ 46 , 47 , 48 , 49 , 50 ]. A recent study indicated that inhibition of the Wnt/β-catenin pathway in the presence of DTX in PCa cells downregulated genes linked to chemoresistance [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with continuous research in the field of molecular biology, CSCs have been found to play an important role in tumor development, invasion, metastasis, chemoresistance, and radioresistance [22][23][24]. The repopulation and differentiation of CSCs often lead to disease recurrence and play an important role in poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…More frequently, aberrant Wnt secretion is associated with cancer progression or tumour immune response in various tissues ( Table 1 ) (reviewed by Galluzzi et al, 2019 , and Katoh and Katoh, 2022 ). Mutations in Wnt pathway components are especially abundant in colorectal cancer, affecting nearly all clinical cases ( Cancer Genome Atlas Network, 2012 ; Yaeger et al, 2018 ; Zehir et al, 2017 ; Zhan et al, 2017 ).…”
Section: Wnt Export Organ Development and Diseasementioning
confidence: 99%